Composite differential evolution algorithm for SHM with low carrier ratio. Issue 6 (1st May 2018) - Yu, Yanjun; Zhang, Pengfei; Song, Zaixin; Chai, Feng
Abstract : This study presents a new method of switching angle solution based on composite differential evolutions (CoDE) in selective harmonic mitigation pulse width modulation (SHMPWM). The method can effectively improve the global searching ability and convergence rate of the solution by the combination of multiple composite trial vectors and control parameter settings. Its great generality makes itself applicable to selective harmonic elimination PWM and synchronous harmonic optimum PWM as well. This study introduces the basic principles of SHMPWM and CoDE, constructs the constraint and objective functions by means of penalty, and gives detailed solution steps. After getting the switching angle solutions from comparative studies including different switching angle numbers, different modulation degrees, or different optimised PWM methods, the experimental platform finally has been designed and carried out to verify the accuracy and generality of the proposed method.